1990
DOI: 10.1288/00005537-199003000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition ability as a function of duration of deafness in multichannel cochlear implant patients

Abstract: Surgical implantation of a multichannel cochlear prosthesis has become a widespread treatment for profound hearing loss. The relationship between duration of hearing loss and speech recognition ability was examined in 20 postlinguistically deafened adults using the Nucleus 22-Channel Cochlear Prosthesis. Data analysis indicated statistically significant negative correlations between duration of profound hearing loss and postoperative performance on the Central Institute for the Deaf Everyday Sentence Test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
0
25
0
1
Order By: Relevance
“…No evidence was found that duration of deafness prior to implantation predicted how quickly a patient arrived at the ceiling. This is surprising, because duration of deafness has been overwhelmingly demonstrated to predict postimplantation outcome [11,12]. On the other hand, our data suggest that the device type may be an influencing factor.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…No evidence was found that duration of deafness prior to implantation predicted how quickly a patient arrived at the ceiling. This is surprising, because duration of deafness has been overwhelmingly demonstrated to predict postimplantation outcome [11,12]. On the other hand, our data suggest that the device type may be an influencing factor.…”
Section: Discussionmentioning
confidence: 65%
“…Their mean duration of deafness prior to implantation was 7.7 years (1 month to 31 years). Causes of deafness were otosclerosis (12), meningitis (7), skull fracture (4), ototoxic medication (4), Cogan syndrome (2), cholesteatoma (2), Ménière's disease (1) and unknown in 48 patients. The patients participated in 6 test sessions: 2 days after initial device activation and then 1 month, 3 months, 6 months, 1 year and 2 years thereafter.…”
Section: Subjectsmentioning
confidence: 99%
“…by affecting an individual's ability to participate in and benefit from rehabilitation [Blamey et al, 1996]). The finding that performance with a CI improves over time [Geier et al, 1999;Hamzavi et al, 2003;Oh et al, 2003;Shea et al, 1990;Waltzmann and Cohen, 1999] is consistent with the proposed role of cognitive factors and suggests that individual differences in verbal learning abilities, as well as in basic verbal cognitive abilities [e.g. processing speed and working memory (WM)], may account for at least some of the large proportion of the variance in CI outcome yet to be explained.…”
Section: Introductionmentioning
confidence: 73%
“…More recent research, however, has found a greater range of improvement, with the considerable variability in outcome partly explained by differences in duration of hearing loss and age at time of implantation [Sarant et al, 1994;Schramm et al, 2002;Teoh et al, 2004;Waltzmann and Cohen, 1999]. Among postlinguistically deafened adult CI recipients, the strongest predictors of success appear to be age at onset of hearing loss [Kaplan et al, 2003], duration of hearing loss [Blamey et al, 1996;Geier et al, 1999;Hamzavi et al, 2003, Oh et al, 2003Shea et al, 1990; UK Cochlear Implant Study Group, 2004] and age at implantation [Blamey et al, 1996;Tyler and Summerfield, 1996]. Etiology has been found to predict outcome to a lesser degree [Blamey et al, 1996;Geier et al, 1999;Loeb and Kessler, 1995;Tyler and Summerfield, 1996;Waltzmann et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the published literature indicate that older age at implantation relates to poorer audiological outcomes [15,16]. Most studies examining the specific effect of age however have not shown any significant effect [4,17,18]. One study suggested a difference between adults and children in the first six months, with comfort levels showing significant change but beyond six months the levels were stable [19].…”
Section: Agementioning
confidence: 99%